(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The work carried out studies of the parameters of the cardiac cycle in karatekas up to different ages and different qualifications, where, under the influence of various physical loads, it makes it possible to judge morphological and functional changes that reflect the process of adaptation of the circulatory system to regular physical loads, characterized primarily by the work of the heart at rest and its high performance in various types of work. A pattern of changes in the parameters of the cardiac cycle was revealed depending on the level of fitness (juniors - up to 20 years old), active athletes (up to 35 years old). With different physical loads, different age groups, the R, S, T teeth were the most variable.